Serratia liquefaciens Causing Severe Ocular Damage in Noncontact Lens Wearer. (September 2018) - Ranganatha, Akshatha; Rana, Mrinal; Murray, Aidan
Abstract : Abstract: Serratia liquefaciens is a rarely encountered gram-negative organism in ophthalmology practice. The only reported ocular infections are from contamination of contact lenses. The authors report the first case of a patient who developed orbital cellulitis secondary to severe S. liquefaciens microbial keratitis.